2001
DOI: 10.1016/s0926-3373(00)00195-8
|View full text |Cite
|
Sign up to set email alerts
|

Strong promotional effects of Li, K, Rb and Cs on the Pt-catalysed reduction of NO by propene

Abstract: The catalytic activity and selectivity of Pt dispersed on ␥-Al 2 O 3 for the reduction of NO by propene is promoted extremely strongly by Li, K, Rb and Cs alkalis in a wide temperature range ca. 450-800 K. Remarkable and unprecedented effects on both activity and selectivity are found. The best promotion effects are achieved by Rb-promotion, for which rate increases as high as 420-, 280-and 25-fold are obtained for the formation rates of N 2 , CO 2 and N 2 O, respectively, in comparison with the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…As a matter of facts, it has been reported that the addition of Na or Ba to supported Pt catalysts results in increase in NO x reduction activity in the absence of oxygen [3,10,11]. According to the mechanism previously suggested (reactions (1)-(3)), it may be argued that the presence of the alkaline or earth-alkaline metal ion weakens the N-O bond, leading to more easy dissociation and subsequent reduction.…”
Section: Reactivity Of Gaseous No In the Presence Of H 2 : Tpr Experimentioning
confidence: 98%
“…As a matter of facts, it has been reported that the addition of Na or Ba to supported Pt catalysts results in increase in NO x reduction activity in the absence of oxygen [3,10,11]. According to the mechanism previously suggested (reactions (1)-(3)), it may be argued that the presence of the alkaline or earth-alkaline metal ion weakens the N-O bond, leading to more easy dissociation and subsequent reduction.…”
Section: Reactivity Of Gaseous No In the Presence Of H 2 : Tpr Experimentioning
confidence: 98%
“…Konsolakis et al showed that the NO reduction on Pt/£-Al 2 O 3 catalyst was promoted by addition of Li (0.164.7 wt %), K (0.98.8 wt %), Rb (1.915.5 wt %) and Cs (3.024.0 wt %) for C 3 H 6 NO reaction. 14) In this case, NO conversion and N 2 selectivity were increased by addition of alkali metals. It seems that the catalytic activity of PGM catalyst for NO reduction is promoted by basicity of the catalyst.…”
Section: Introductionmentioning
confidence: 82%
“…alkalies, can drastically enhance both the de-NO x activity and N 2 -selectivity of both Pt and Pd. Hydrocarbons and CO oxidation reactions were also significantly enhanced by the same way [3][4][5][6].…”
Section: Introductionmentioning
confidence: 90%
“…The origin of the promotional effects of Na on TWC catalytic chemistry is not the object of the present study; the way of action of Na modifier has been extensively investigated in previous detailed kinetics and spectroscopic studies where the origins of the promoting phenomena have been well rationalized [3][4][5][6]. The main object of this paper is to record the performance of these materials in more realistic conditions and in the form that they are used in practical applications.…”
Section: No Reductionmentioning
confidence: 99%